PEMANFAATAN WAKTU SENGGANG BAGI PESERTA DIDIK DI SMA PERTIWI 1 PADANG - Dasvita, Melda Krisna; Syarif, Mellyarti; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
This research based on activities from the learners at SMA 1 Pertiwi. Based on studies in initial interview, it was revealed that the learners after school just spend the time to playing with friends to his favorite places. Focus of this research were: the utilization of spare time to rest, entertainment and personal development. This research was a descriptive qualitative research. To take the sampling researcher used snowball sampling. Key informants in research was students. Additional informants were family and friends as same ages. Data were collected through interviews, observation and documentation. This data is tested by holding triangulation and membercheck, after that, it was analyzed by three stages: 1. Data reduction, 2. Presentation of data, 3. Conclusion. The results of this research was revealed that utilization of leisure time commonly more often spent napping, online and other activities that are not meaningful. Free time for entertainment more often spent playing and doing other activities that are not useful. Free time for personal development is indeed widely used by students, but the students did not seriously follow it so that the activities carried out not productive. Based on this research, the learners must utilization their time for useful activities.